Escala de Satisfação no Domínio Académico em Universitários Portugueses - Almeida, Leandro (2020)
Students’ satisfaction has been valued as an indicator of the quality of higher education institutions, and as a relevant variable in explaining their involvement, learning and persistence. Satisfaction, associated to the diverse contexts of students' academic experience, is understood as a construct of students’ evaluation of the institution, academic climate, course and interpersonal relationships. Based on a sample of students from two Portuguese Higher Education institutions, one public and another private, we analyze the validity evidence of the Academic Domain Satisfaction Scale. The results of a confirmatory factorial analysis suggest the one-dimensional nature of the scale. On the other hand, adequate levels of internal consistency of its items, as well as significant correlations between the result in the scale and indicators of the students' affective disposition, academic performance and dropout intentions, point towards the validity of the measure.